Possibility of Neoplastic Transformation of Ovarian Endometriosis - A. Levakov , Sergey; A. Gromova, Tatyana (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was to investigate the features of neoplastic endothelial transformation in the foci of ovarian endometriosis (OE).Materials and Methods: Histologic and immunohistochemical methods were used for the study of 78 and 35 cases of OE, respectively, and 8 cases of adenocarcinomas. The authors used antibodies to Ki-67, Всl-2, р53, and nuclear hepatocytes factor 1 beta (HNF-1β).Results: Epithelial walls of endometrial cysts had syncytial papillary changes (39.7%), metaplasia with hobnaillike cells (15.4%), atypia of epithelium with fluctuation of the expression of Ki-67 and Всl-2 from low to relatively high (41.0%), and the expression of р53 that tended to increase. The expression of HNF-1β in lesions without atypia was revealed in 56.3% of cases, and in lesions with atypia—in 94.7%, and was identified only in clear cell adenocarcinomas.Conclusion: Hyperexpression of HNF-1β suggested adaptive character and histogenetic association of OE with clear cell ovarian tumors.